Human Resource Development Strategies to Enhance Small Business Economic Growth in Community Settings - Sutrisno, Sutrisno; Siminto; Ausat, Abu Muna Almaududi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Human resource development (HRD) is a key factor in driving economic growth, particularly among small businesses. Skilled and competent human resources can enhance productivity and efficiency, thereby fostering faster economic growth. This research aims to identify and analyze effective HRD strategies in boosting the economic growth of small businesses within community settings. This study employs a literature review method with a qualitative approach and descriptive analysis. Data sourced from Google Scholar span publications between 2001 and 2024. Findings indicate that HRD plays a crucial role in enhancing the economic growth of small businesses within communities. Skilled and trained human resources can elevate productivity, efficiency, and innovation, thus enhancing the quality of products and services offered and business competitiveness. including access to education, financial limitations, and inadequate infrastructure. Effective HRD strategies should address these challenges through educational and training programs, improving working conditions, leadership development, and collaboration among stakeholders